Decomposição de amostras botânicas e leite em pó utilizando peróxido de hidrogênio em sistema de alta pressão e posterior determinação elementar por ICP OES e ICP-MS - Müller, Cristiano Cabral (2016)
Recently, there is an appeal to reduce the use of toxic reagents in a great effort for the development of analytical "green" methods. Thus, the paper proposes the elemental analysis of botanical and food samples without the use of toxic reagents such as HNO3 in sample preparation step. In this thesis, the use of H2O2, which is considered a "green" reagent was evaluated for the decomposition of espinheira-santa samples (Maytenus Maytenus), guarana (Paullinia cupana) and milk powder samples with different percentages of carbohydrates, proteins and fats. In the first step of this study, tests were performed to evaluate the H2O2 behavior as a single oxidizing agent for decomposition of espinheira-santa in 3 different sample preparation systems: (1) the digestor block (2) Multiwave 3000 and (3) UltraWave -SRC. The results of these tests, there is the need to use a sample preparation system capable to achieve pressures greater than 100 bar to obtain digests without the presence of insoluble residues and concentration C of less than 1000 mg L-1 when 250 mg of espinheira-santa were decomposed. From this observation, the UltraWave-SRC system was required for other optimization tests since it can withstand a pressure up to 199 bar. In the optimization step, was evaluated the effects of sample mass, H2O2 concentration and molar ratio of H2O2 and carbon contained before decomposition. The optimization method led to obtaining digested efficiently decomposed (C concentration < 1600 mg L-1) even when 1250 mg of espinheira-santa underwent decomposition with H2O2 30% m/m. With the success of the tests for decomposition espinheira-santa and guarana samples, was conducted the study with milk powder samples, which have in their composition high levels of proteins and fats. Employing the UltraWave-SRC system with H2O2 for milk powder decomposition was possible to complete decomposition using 500 mg of sample. As expected, the concentration of C in powdered milk digested were higher than the concentrations observed in digested of espinheira-santa, probably due the milk powder samples has a high fat content (> 20%). Subsequent to these findings proceeded to the optimization of the method proposed for powdered milk. In these tests, was used a sample of powdered milk with higher fat content between samples assessed for to study the parameters temperature and maximum pressure, the concentration of H2O2 and the sample mass. Digested of milk powder with lower concentrations of C (< 918 mg L-1) was obtained using the highest temperature and pressure of 250 °C and 199 bar, respectively, the sample mass of 500 mg and 8 mL of H2O2 50% m/m. The accuracy of the method was assessed by using the NIST 1515 certified reference material (leaves Apple), IAEA V9 (Cotton cellulose), NIST 8435 (Whole Milk) and NIST 1549 (Non fat milk powder) with the proposed method. No significant differences were observed for a significance level of 95% (Studant t test) when the certified values and the results were compared. Significant interferences were not observed in the elemental determination in all samples when the techniques of optical emission spectrometry with inductively coupled plasma (ICP OES) and mass spectrometry with inductively coupled plasma (ICP-MS) were used. Thus, the proposed method allows the quality control of botanical samples and milk powder with respect to the elemental determination. Furthermore, the detection limits of the proposed method meet the requirements of official compendia, in particular with regard to the determination of this toxic elements. The developed method can be considered friendly from an environmental point of view, due to this not employ toxic reagents.